UPACARA ADAT KENDUHAI SKO PADA MASYARAKAT KERINCI PROVINSI JAMBI - Deria Sepdwiko (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
Research aimed to reveal the ceremonial KenduhaiSko in Kerinci community precisely in the Sungai Penuh. The research is a qualitative research method of interpreting. The object of this study is KenduhaiSko ceremonial. The technique of collecting data is collected through library research, observation, interviews, and documentation. The data analysis technique based on the results of the study stated that etnografi.Temuan ritual ceremonies for the community KenduhaiSko River City Full aesthetic significance. SkoKenduhai can be interpreted in the traditional party held aiming to unite the community such as the appointment of customary title. Of course with the event KenduhaiSko interweave solidarity and enforced for the survival of the ceremony, and this participation can be a contribution of thought and energy costs, as well as objects or equipment necessary for the provision of ceremonial KenduhaiSko.